Information, Asymmetric Incentives, or Withholding? Understanding the Self-Enforcement of Value-Added Tax - Mazhar Waseem (Center for Economic Studies and ifo Institute (CESifo), 2019)
During the period 1996-2000, the coverage of VAT in Pakistan rose by twenty times in terms of the number of firms in the tax net and by ten times in terms of the volume of transactions subject to it. This paper leverages this staggered introduction of VAT in the country to estimate its enforcement spillovers. Focusing on firms already in the tax net, I explore if their tax compliance improves as VAT gets extended to their trading partners. Using differential responses to upward and downward extension of the tax, I characterize the mechanisms underlying the self-enforcement response.
Keywords: H25; H26; O17; 330; VAT; tax evasion; informality